SELECTING SEEDING TECHNIQUES AND PLANT MEDIA TO PRODUCE GENERATION ZERO (G0) TUBERS OF PORANG (Amorphophallus muelleri Blume) - Imaniah Bazlina Wardani; Nunung Harijati (Journal of Environmental Engineering and Sustainable Technology, 2020)
Provision of seedlings A. muelleri in bulk can be done using seeds. The problem is seeds A.muelleri will be die if planted directly in the field. That caused seeds losing competition with weeds. So  needs a treatment to grow the seeds until zero generation (G0) tubers is formed. The technique used to maximize the formation of G0 tubers A. muelleri is selection of seed types and planting media. There are 3 types of seeds used, namely R  (red fruit seeds), Y (yellow fruit seeds) and G (green fruit seeds) where each type has a different level of maturity. Meanwhile there are 4 types of planting media used, namely M1 (soil: husk charcoal), M2 (soil: cocopeat), M3 (soil: cocopeat: husk charcoal) and M4 (soil). Every R, Y and G seeds were planted on M1, M2, M3 and M4 media. The parameters observed were weight, thickness and diameter of the G0 tubers. The data obtained were analyzed with 5% ANOVA and if there were differences followed by the 5% Tukey test. The results showed that the best G0 tubers were produced from planting R type seeds on M3 (RM3) media weighing 3.63 grams but were not significantly different from the treatment of planting R type seeds on media M1 (RM1) which was weighing 3.06 grams.